Reintroduction of North Island robins to Paengaroa Scenic Reserve : factors limiting survival, nest success, and population viability in a mainland restoration area : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University - Raeburn, Elizabeth Helen (Massey University, 2001)
Forty North Island robins (Petroica australis longipes) were reintroduced to Paengaroa Scenic Reserve in March 1999. I monitored the survival and breeding success of this population for two years post-release. This study aims to assess survival, nest success, and population viability of robins in Paengaroa in an attempt to discover whether habitat in the reserve is likely to support a population of robins. Survival from the time of release to the start of the first breeding season was lower at Paengaroa than at two other release sites, Boundary Stream Scenic Reserve and Tiritiri Matangi Island. This may be due to higher predator levels at Paengaroa or dispersal out of the reserve. Methods of estimating nest success were compared, and Stanley's (2000) method was found to have advantages over the traditional and Mayfield methods. Daily survival rates of nests at Paengaroa depended on both the stage in the nesting cycle and stage of the breeding season, with the survival rate lowest for early nests at the incubation stage. Nest success for the first two breeding seasons after translocation was compared to that for the first two seasons after release at Tiritiri Matangi and Boundary Stream. Paengaroa had a similar nest success rate to Tiritiri Matangi (25% and 26% respectively), and both of these sites had lower nest success than Boundary Stream (47%). Survival at Paengaroa was most affected by whether a bird was recently-translocated. a juvenile, or an adult. Recently-translocated birds and juveniles suffered similarly low survival rates, suggesting that this high mortality may be due to problems faced when finding and establishing a territory. The survival of juveniles from January to September was estimated to be 29%. The annual adult survival rate was also low (59%). Fecundity and survival estimates were used in a stochastic simulation model to predict the viability of the Paengaroa population. Under current conditions, the population was predicted to have a 17% probability of surviving 10 years. However, variation of parameters to lower and upper 95% confidence limits gave survival probabilities of 0% to 100% over 10 years. When data from the first year after translocation were excluded, the population was predicted to have a 100% probability of surviving 100 years. These results demonstrate the large uncertainly associated with small sample sizes and short-term studies. To assess whether habitat quality is likely to account for the poor overall viability predicted at Paengaroa, the habitat quality at Paengaroa was compared to that at Waimarino forest, where robins still persist. Food supply and predator levels were used to assess habitat quality, as these are obvious factors that may limit viability. Data on food and predator levels provided no indication of why robins may be non-viable at Paengaroa. The power of statistical tests was low due to small sample size, but results suggest Paengaroa has more food as well as fewer rats and stoats than Waimarino. There is a need for further research to improve our understanding of why robins are present and common in some mainland areas but have disappeared from others without any obvious difference in habitat quality. Continued research is also required to reduce the uncertainty regarding population viability at Paengaroa and to determine whether improved management is needed.
Keywords: Paengaroa Scenic Reserve; North Island robin; Rare birds; Bird populations; Wildlife relocation; New Zealand -- North Island; Adaptation